Metabolomic fingerprinting based on network analysis of volatile aroma compounds during the forced aging of Huangjiu: Effects of dissolved oxygen and temperature - Wang, Na; Zhang, Lili; Ren, Xuejiao; Chen, Shuang; Zhang, Zhen (Frontiers in Nutrition, 2023)
Introduction Huangjiu is an important Chinese alcoholic beverage, usually prepared from rice. Although its unique flavor improves with prolonged storage in traditional pottery jars, knowledge of the aging mechanism, necessary for commercialization of an optimum product, remains unclear. Methods Here, volatile aroma compounds from forced aged samples exposed to different temperatures and oxygen treatments were measured by GC/MS. After retention time alignment and normalization, the peak vectors were compared over storage time using Pearson's correlation, and a correlation network was established. Marker compounds, representative of traditionally aged Huangjiu, were then monitored and compared to similar compounds in the forced aged product. Results and discussion Correlation network analysis revealed the following: Temperature had little effect on most aroma compounds; alcohols, acids, and esters all increased with increasing dissolved oxygen, while polyphenols, lactones, and ketones were readily oxidized; aldehydes (e.g., furfural and benzaldehyde) were highly dependent on both temperature and dissolved oxygen. Dynamic changes in the targeted aging-markers showed that a higher initial oxygen concentration intensified the “aging-aroma” of Huangjiu in the early and middle stages of storage. Consequently, careful control of oxygen supplementation and storage temperature could be beneficial in controlling the desirable flavor of Huangjiu in the artificially aged product.